Case report : A rare cause of upper airway obstruction - Mahno, Noor Ezmas; Mohammad Saukani, Mohd Faizal; Soe, Yan Naing; Yusof, Mubarak (2012)
Malignant fibrous histiocytoma (MFH), is a malignant sarcoma of uncertain origin that may arise either from soft tissue or bone. It was first described by Kauffman and Stout in 1961 as tumor rich of histiocytes and storiform growth patern. No true cell of origin has ever been identified. In 2002, World Health Organization (WHO) renamed MFH as undifferentiated pleomorphic sarcoma, not otherwise specified, NOS. Despite that, it was the most common soft tissue sarcoma in adult. Soft tissue MFH can arise in any part of the body but lower extremity is the most common site and it is very uncommon to arise from the head and neck.